TINJAUAN TERHADAP PENERAPAN PURCELL PRINCIPLE DALAM PUTUSAN MAHKAMAH KONSTITUSI (ANALISIS TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 & PUTUSAN NOMOR 60/PUU-XXII/2024) - Moch. Alfin Fauzan Ismail (Yayasan Pendidikan Islam Almatani, 2025)
The presence of the Constitutional Court's decision testing the constitutionality of norms surrounding elections when the election stages have begun is a serious problem that must be observed together. The involvement of the Constitutional Court in examining and adjudicating political cases, especially those related to elections, makes the Constitutional Court involved in the process of judicializing politics. In addition, based on the concept of the Purcell principle, the Constitutional Court should not decide cases that have an impact on election rules, especially if the election stages have begun or are ongoing. The absence of the Purcell principle in several Constitutional Court decisions will basically make it difficult for election organizers to adjust election rules and have an impact on confusion in society. This situation has also indirectly shown the role of the judiciary which is so strong in the process of judicializing politics. So based on the description, this article is presented with the intention of looking at the process of political judicialization carried out at the Constitutional Court, as well as looking at the application of the Purcell principle in two decisions related to the implementation of the 2024 election, namely the Constitutional Court Decision Number 90/PUU-XXI/2023 and the Constitutional Court Decision Number 60/PUU-XXI/2024. This research is a normative legal research with a literature study. So that the data and materials obtained will be analyzed qualitatively. The results of this study indicate that the Constitutional Court appears active in carrying out political judicialization, in handling tests related to election regulations. In the Constitutional Court Decision Number 90/PUU-XXI/2023 and the Constitutional Court Decision Number 60/PUU-XXI/2024, the Constitutional Court tends to ignore the application of the Purcell principle in the two a quo decisions. Kehadiran putusan Mahkamah Konstitusi yang menguji konstitusionalitas norma seputar pemilu pada saat tahapan pemilu telah dimulai menjadi masalah serius yang harus dicermati bersama. Keterlibatan Mahkamah Konstitusi untuk memeriksa dan mengadili perkara-perkara politik, khususnya yang berkaitan dengan pemilu, membuat Mahkamah Konstitusi terlibat dalam proses yudisialisasi politik. Disamping itu, berdasarkan konsep purcell principle, Mahkamah Konstitusi seharusnya tidak memutus perkara yang memiliki dampak terhadap aturan pemilu, apalagi jika tahapan pemilu tersebut telah dimulai atau sedang berlangsung. Ketidakhadiran purcell prinsiple dalam beberapa putusan Mahkamah Konstitusi pada dasarnya akan menyulitkan para penyelenggara pemilu dalam menyesuaikan aturan pemilu dan berdampak pada terjadinya kebingungan pada masyarakat. Keadaan tersebut juga secara tidak langsung telah menunjukan peran lembaga peradilan yang begitu kuat dalam proses yudisialisasi politik. Sehingga berdasarkan uraian tersebut, tulisan ini hadir dengan maksud melihat proses yudisialisasi politik yang dilakukan di Mahkamah Konstitusi, sekaligus melihat penerapan purcell principle dalam dua putusan yang berkaitan dengan penyelenggaraan pemilu 2024, yakni Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 dan Putusan Mahkamah Konstitusi Nomor 60/PUU-XXI/2024. Adapun penelitian ini merupakan penelitian yuridis normatif dengan studi kepustakaan. Sehingga data dan bahan yang diperoleh akan dianalisis secara kualitatif. Hasil penelitian ini menunjukan bahwa Mahkamah Konstitusi terlihat aktif didalam melakukan yudisialiasai politik, dalam menangani pengujian yang berkaitann dengan regulasi pemilu. Dalam Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 dan Putusan Mahkamah Konstitusi Nomor 60/PUU-XXI/2024, Mahkamah Konstitusi cenderung mengabaikan penerapan purcell principle dalam dua putusan a quo.